2023
DOI: 10.1089/thy.2022.0304
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genetic Link Between Thyroid Dysfunction and Common Psychiatric Disorders: A Specific Hormonal or a General Autoimmune Comorbidity

Abstract: Background: The hypothalamus-pituitary-thyroid axis coordinates brain development and postdevelopmental function. Thyroid hormone (TH) variations, even within the normal range, have been associated with the risk of developing common psychiatric disorders, although the underlying mechanisms remain poorly understood. Methods: To get new insight into the potentially shared mechanisms underlying thyroid dysfunction and psychiatric disorders, we performed a comprehensive ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The absence of nocturnal TSH surges has been noted in depressed patients, and lower basal TSH levels have been reported more in patients with major depression than in those without major depression [18]. Genetically, a strong coherence was observed between thyroid disease and both major depressive disorders, and this genetic correlation was particularly strong at the major histocompatibility complex locus on chromosome 6 [19]. However, an observational study suggested that depressive symptoms should not be attributed to minor variations in thyroid function [20].…”
Section: Original Papermentioning
confidence: 99%
“…The absence of nocturnal TSH surges has been noted in depressed patients, and lower basal TSH levels have been reported more in patients with major depression than in those without major depression [18]. Genetically, a strong coherence was observed between thyroid disease and both major depressive disorders, and this genetic correlation was particularly strong at the major histocompatibility complex locus on chromosome 6 [19]. However, an observational study suggested that depressive symptoms should not be attributed to minor variations in thyroid function [20].…”
Section: Original Papermentioning
confidence: 99%
“…Furthermore, hypothyroidism can also impair cognitive functions [4], which can hinder the brain's ability to support higher functions due to inadequate energy consumption [5]. Thyroid hormones play a vital role in the adult brain, and it is widely accepted that clinical hypothyroidism can lead to psychological [6,7] and psychiatric symptoms [8][9][10], as well as autonomic imbalance [11].…”
Section: Introductionmentioning
confidence: 99%
“…O ur publication in the February issue of Thyroid 1 has led to a lively discussion on the relations between thyroid (dys)function, psychiatric disorders, and its potential genetic and autoimmune underpinnings. In an accompanying commentary Nygaard systematically reviewed pitfalls in available literature and knowledge gaps to overcome.…”
mentioning
confidence: 99%